A study of redesigning food delivery application in Thailand - Pongsatorn Sungboonlue; Satisa Thanakaew; Kittisak Rangseepanya; Teramate Tangpatong; Thitirat Siriborvornratanakul (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
User interface (UI) and user experience (UX) design is fundamental to the stickiness of any application. Food delivery is no exception. With the food delivery business sector on the rise during the coronavirus disease 2019 (COVID-19) pandemic, it is necessary for any newcomers in the market to at least match the must-have feature lists of the major players. However, Robinhood, despite having a niche in societal responsibility, is still a food delivery app that is found to lack some of the features that, in the past few months, due to the fierce competition within the food delivery space, moved down from a delighter to a must-have. In this paper, we show, through iterations of qualitative interviews, the proposed solutions consisting of features and future roadmap along with the general context of why each implementation was selected in each sprint. Through all these experiments, we learned not to go against the natural reading pattern of reading from left to right, the z pattern in the visual hierarchy, the users’ familiarity with buttons placement due to loaded external factors, and how introducing too many new features may negatively impact the usability test score.